Modeling and controller design of an industrial hydraulic actuator system in the presence of friction and internal leakage - Rahmat, Mohd Fua'ad; Has, Zulfatman; Husain, Abdul Rashid; Md Sam, Yahya; Ishaque, Kashif; Ghazaly, Rozaimi; Md Rozali, Sahazati (http://www.academicjournals.org/IJPS, 2011)
This paper presents a robust controller scheme and its capabilities to control the position tracking performance of an electro-hydraulic actuator system. Sliding mode control with fixed and varying boundary layer is proposed in the scheme. It is aimed to compensate nonlinearities and uncertainties caused by the presence of friction and internal leakage. Its capabilities are verified through simulations in Matlab Simulink environment. The friction was represented by the LuGre model and the internal leakage was assumed to change. The results indicate that the scheme successfully improves the robustness and the tracking accuracy of the system. This improvement offers a significant contribution in the control of modern equipment positioning applications.